12x * 4x2 = 48x3
Chat with our AI personalities
4x2 - 12x + 9 = 5; whence, 2x - 3 = ±√5, and 2x = 3 ±√5. Therefore, x = ½ (3 ±√5).
Factor the equation and solve for x in each part. x3-4x2-12x Factor out an x right away x (x² - 4x - 12) factor the trinomial x (x - 6) (x + 2) now solve each for y=0 x=0, (x-6=0), (x+2=0) The zeroes (solutions) to the equation are {-2 0 6 }■
It could be either of them.
If you mean: 4x squared+12x+9 then it is (2x+3)(2x+3)
4x2 - 12x + 9 = 4x2 - 6x - 6x + 9 = 2x(2x - 3) - 3(2x - 3) = (2x - 3)(2x - 3) or (2x - 3)2